Monocarboxylate transporter 4 inhibition potentiates hepatocellular carcinoma immunotherapy through enhancing T cell infiltration and immune attack. Issue 1 (7th January 2023) - Fang, Yuan; Liu, Weiren; Tang, Zheng; Ji, Xiang; Zhou, Yufu; Song, Shushu; Tian, Mengxin; Tao, Chenyang; Huang, Run; Zhu, Guiqi; Jiang, Xifei; Gao, Jun; et al.
Abstract : Background and Aims: Monocarboxylate transporter (MCT) 4 is a high‐affinity lactate transporter that is primarily involved in the maintenance of intracellular pH homeostasis and highly expressed in different tumors. However, the role of MCT4 in modulating immune responses against HCC remains unknown. Approach and Results: In this study, we demonstrated that MCT4 was overexpressed in HCC, which was associated with poor prognosis in patients. Genetic or pharmacological inhibition of MCT4 using VB124 (a highly potent MCT4 inhibitor) suppressed HCC tumor growth in immunocompetent mice model by enhancing CD8 + T cell infiltration and cytotoxicity. Such improved immunotherapy response by MCT4 targeting was due to combined consequences characterized by the alleviated acidification of tumor microenvironment and elevated the chemokine (C‐X‐C motif) ligand (CXCL) 9/CXCL10 secretion induced by reactive oxygen species/NF‐κB signaling pathway. Combining MCT4 inhibition improved the therapeutic benefit of anti–programmed cell death 1 immunotherapy in HCC and prolonged mice survival. Moreover, higher MCT4 expression was observed in tumor tissues from nonresponder patients with HCC receiving neoadjuvant therapy with toripalimab. Conclusions: Our results revealed that lactate exportation by MCT4 has a tumor‐intrinsic function in generating an immunosuppressive HCC environment and demonstrated the proof of the concept of targeting MCT4 in tailoring HCC immunotherapeutic approaches. Abstract :